An overview of the effects of physical exercise programs on individuals with Intellectual and Developmental Disabilities - Miguel Jacinto; José Pedro Ferreira; Diogo Monteiro; Raul Antunes; Maria João Campos; Rui Matos (Desafio Singular, 2024)
Being aware of the relevance of physical exercise in individuals with Intellectual and Developmental Disabilities (IDD), we intend to conduct a brief review on the importance of regular physical exercise for this population. An approach will be taken in order to acknowledge the barriers to the high rates of sedentary lifestyles in this population, the potential benefits of physical exercise, and the essential aspects for a correct assessment, prescription, and implementation of these programs in the population with IDD, through a reflection supported by scientific evidence. The current overview aims to provide relevant information regarding the health benefits of physical exercise in individuals with IDD, as the basis for QoL promoting more active and healthier lifestyles, namely through structured physical exercise. In addition, it is also a useful tool for consultation by exercise professionals since adjusted indoor and outdoor exercise programs are listed.